The Effect of Giving Dragon Fruit Juice on Increasing HB Levels in Pregnant Women - Nelly Mariati; Wulandari Wulandari; Mirawati Mirawati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2022)
Nutrition has a big role in determining maternal health. Malnutrition of pregnant women is not only related to malnutrition in the developing fetus, but also directly affects maternal health and the risk of maternal death. There are two critical pathways by which maternal nutrition can affect fetal survival, namely anemia and calcium deficiency. Anemia in pregnant women contributes as much as 20% of maternal deaths and low calcium consumption can lead to gestational hypertension which can trigger preeclampsia and eclampsia, which are the second most common cause of maternal death. Handling anemia by consuming plants such as vegetables and fruits, one of which is dragon fruit. Dragon fruit contains high phytochemicals, namely flavonoids 7.21 mg CE/100 grams. In addition, dragon fruit is a fruit that is rich in antioxidants and relatively high calcium and iron which plays a good role in bone and blood function. The purpose of this study was to analyze the effect of dragon fruit juice on increasing Hb levels in pregnant women. The research method used is Quasi Experiment (quasi-experimental) with pre-test post-test group design. The sampling technique of this research was done by purposive sampling, obtained a sample of 30 respondents consisting of 15 respondents from the intervention group and 15 respondents from the control group. The results showed that there was an effect before and after being given dragon fruit juice, the test used a paired t test where it was obtained for the intervention group p value 0.001 and for the control group p value 0.011. The intervention administration of Fe tablets and dragon fruit juice increased the Hb level of pregnant women by 1.42 g/dl, while the administration of Fe tablets only gave an increase of 1.2 g/dl. Keywords: pregnant mother, Dragon fruit juice, Hemoglobin